Result of Law on Construction of Flats which are Granted Ownership Rights Over the Building Use Rights - Khoeron Khoeron (Sultan Agung Notary Law Review, 2020)
The study, entitled "The Legal Consequences for the Construction of Flats Which Are Given Ownership Status over Building Use Rights in the City of Semarang" in order to find out and analyze legal protection for apartment owners with ownership rights over building use rights and legal consequences of building flats with ownership rights above the right to build. This study uses an empirical juridical approach, which is a legal research conducted by examining and analyzing existing facts in line with observations in the field. Legal protection of ownershipownership rights to flats above the right to use the building, of course based on evidence of legal certainty obtained by the owner of the apartment unit in the form of a certificate of ownership of the apartment unit. Ownership of one flat is certainly owned by each individual who owns the flat with horizontal and vertical separation principles. The regulation regarding the right to build itself explains that the legal consequence of the expiration of the term of the right to build will result in land falling to the state so that each resident of the apartment with the joint management of the apartment must still pay attention to the period of time for the unit belonging to the apartment. The legal consequence of the construction of a flat above the right to build is that based on the principle of horizontal separation so that there is proof of ownership of the apartment which is explained in the certificate that the ownership rights to the apartment unit are not eliminated provides a certainty of ownership of the apartment. The status of the apartment on the right to build will certainly result in each resident of the apartment paying the cost of extension of the building use right because in this case if the right to use the building ends it will have an impact on the status of the land that is jointly owned in the form of public facilities around the house stacking.